An adaptive‐design dose‐ranging study of PD 0348292, an oral factor Xa inhibitor, for thromboprophylaxis after total knee replacement surgery. Issue 8 (14th August 2013) - Cohen, A. T.; Boyd, R. A.; Mandema, J. W.; DiCarlo, L.; Pak, R.; ,
Summary Background PD 0348292 is an oral, selective, direct and reversible factor Xa inhibitor. This was an adaptive dose‐ranging study evaluating a 100‐fold PD 0348292 dose range in subjects undergoing total knee replacement (TKR). Objective To assess the efficacy and safety of a dose range of PD 0348292 relative to enoxaparin for the prevention of venous thromboembolism (VTE). Methods Extensive dose‐response modeling and trial simulations were used to select the PD 0348292 dose range for the Phase 2 study. Subjects were randomized to a blinded PD 0348292 dose (0.1 mg qd to 10 mg qd) or open‐label enoxaparin (30 mg bid) for 6–14 days after TKR surgery. Efficacy was assessed by mandatory bilateral venography. Results were analyzed using a dose‐response modeling approach. Results Observed VTE frequency ranged from 1.4–37.1% across PD 0348292 doses and was 18.1% for enoxaparin. The PD 0348292 dose‐response relationship for VTE was statistically significant (P < 0.0001). The dose of PD 0348292 equivalent to enoxaparin 30 mg bid for VTE prevention was estimated to be 1.16 mg (95% CI = 0.56 mg, 2.41 mg) qd. Total bleeding ranged from 4.9% to 13.8% across PD 0348292 doses and was 6.3% with enoxaparin. The dose‐response relationship for total bleeding was not statistically significant (P = 0.2464). Overall, PD 0348292 and enoxaparin were well tolerated. Conclusion Characterization of the dose‐response relationship for VTE and bleeding using an adaptive Phase 2 study design provided a strong quantitative basis for Phase 3 dose selection.